Surgical Treatment of Velopharyngeal Insufficiency Following Primary Palatoplasty - Jargaldavaa, Erdenetsogt; Gongorjav, Ayanga; Badral, Batbayar; Lkhamsuren, Khentii (Central Asian Journal of Medical Sciences, 2024)
Objective: Identify a better surgical method for primary palatoplasty in a specific cleft type and evaluate outcomes of velopharyngeal insufficiency correction surgery. Methods: A prepost study design was conducted by collecting data from cleft patients’ medical charts used at the National Center for Maternal and Child Health in Mongolia. The Veau classification was used for the type of palatal clefts. Results: 335 cleft palate patients were included in this study. Of the participants, 133 patients were diagnosed with VPI after primary palatoplasty. Of 75.9%, they underwent secondary palatoplasty with a soft palate Z plasty method and 24.1% by a pharyngeal flap technique. The result of the NPS examination postoperatively is as follows: the adequate velopharyngeal function was 97% for the soft palate Z plasty method and 84.4% for the pharyngeal flap technique. (P= 0.021). Conclusion: The Furlow and Mongolian techniques are superior for maintaining velopharyngeal function after primary palatoplasty. For correcting velopharyngeal insufficiency, the secondary soft palate Z plasty and a superior-based pharyngeal flap demonstrate good speech results after surgery.